Manajemen dan Rujukan Sindroma Koroner Akut menggunakan iSTEMI Network - Edrian Zulkarnain (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Acute myocardial infarction (AMI) patients who experience total blockage of the heart arteries accompanied by ST segment elevation on an electrocardiogram (ECG) record, known as ST elevation myocardial infarction (STEMI); one of the leading causes of death in Indonesia. In the STEMI patient care system there are three components that cause delays in handling which lead to an increased risk of death. First, the patient's delay; second, the system delay in the detection of STEMI patients and transfer to capable reperfus facilities; third, delays in health facilities, i.e. the time needed since the patient arrives at the health facility until reperfusion therapy is given, both by fibrinolysis and primary percutaneous coronary intervention. Therefore Palembang needs to prepare an iSTEMI program, so that STEMI patients can be reproduced immediately. ISTEMI management in Palembang requires good organizational management.